Faktor Yang Mempengaruhi Keaktifan Orang Tua Balita Dalam Kegiatan Posyandu Di Puskesmas Sebatung Kabupaten Kotabaru - Fitriani, Indria; Istiqamah , Istiqamah; Avrilina Haryono , Ika (Pusat Riset dan Inovasi Nasional, 2023)
. Posyandu is a forum for monitoring the growth and development of toddlers. Coverage of visits by toddlers to posyandu related to mother's activity. The discrepancy between the attainment of community participation or the irregularity of mothers in visiting Posyandu with the target visit is made possible by several factors including age, education, parity, knowledge, attitudes and family support. The Sebatung Health Center has achieved the service target of 41% of the target of 86.2% in 2021. The objective of this research is to knows the factors that influence the activity of parents of toddlers in posyandu activities. The method used analytical survey method with cross sectional approach. The sample used the accidental sampling technique of 30 mothers with healthy toddlers (age 12-59 months) at the Sebatung Health Center in January 2023. Statistical test analysis using Chi Square. The results are The most research results for each variable are the activeness of parents of toddlers 22 people (73.3%), mothers with good knowledge of 19 people (63.3%), a positive attitude of 18 people (60%), family support of 19 people (63 .3%), there is an effect of knowledge (p=0.004), attitude (0.034) and family support (0.015) on the activeness of parents of toddlers in posyandu activities. Concluded there is an influence of knowledge, attitudes and family support on the activeness of parents of toddlers in posyandu activities.